Thoracotomy: An Overview of Perioperative Anaesthetic Management - Solanki, Nilesh Maganbhai; Engineer, Smita; Shah, Namrata; Mistry, Nirmal; Tamilanban, Soundarya (Journal of Anaesthesia and Pain, 2024)
Background: The anesthesiologist's role during open thoracotomy includes using a double lumen tube (DLT) for lung isolation, maintaining oxygenation with one-lung ventilation (OLV), and providing postoperative analgesia. This study aims to describe patient demographics, comorbidities, perioperative anesthetic management, complications, and the effectiveness of epidural catheter analgesia.Methods: In this prospective, observational study, patients who underwent open thoracotomy for decortications were evaluated. Thoracotomy was done under general anaesthesia, OLV with DLT, and epidural analgesia. Postoperatively, all the patients were shifted to the intensive care unit. Collected data included patient demographics, associated co-morbidities, severity of lung diseases, complications, and postoperative recovery. Postoperative analgesia was assessed by the visual analogue scale (0-10).   Result: Of 20 patients, 16 were male, and 4 were female, with a mean age of 35 years (range 15-60) and a mean weight of 52 kg (range 36-66). History of hypertension (N=5), hypertension with diabetes (N=3), obstructive lung disease (N=6), restrictive lung disease (N=11), and both combined (N=3) were noted on pre-anesthetic check-ups. Intraoperative complications were hypotension (N=3), desaturation (N=3), respiratory acidosis (N =7), and metabolic acidosis (N=3). Postoperative analgesia was managed with an epidural catheter (N=18) & systemic analgesia (N=2). All patients had uneventful postoperative courses except one patient who had pulmonary edema and did not survive.Conclusion: Patients undergoing open thoracotomy had an increased risk for adverse perioperative outcomes. The incidences of perioperative morbidity are high in patients with associated comorbidities. Proper OLV strategy helps to correct intraoperative desaturation. Epidural analgesia plays a key role in postoperative recovery.